TONGKONAN SEBAGAI PUSAT LITERASI PENUNJANG PEMBELAJARAN BAGI SISWA DIDIK DI KELURAHAN PANGALA - Olivia Devi Y. Pompeng; Rahma G. Tammu; Elisabet Pali; Astriwati Biringkanae; Lisa Kurniasari Wibisono (Yayasan Education and Social Center, 2023)
Pangala' is one of the Villages in North Toraja South Sulawesi, Pangala' Village, Rindingallo District has 4 Neighborhoods namely, Tanga Tondok Neighborhood, Batan Pa'pararukan, Tondon Pasar, and Tandungallang Neighborhood. In the Pangala sub-district, livelihoods are the main focus of the community so that education for children is no longer given full attention. In addition, the increasingly developing science of technology is also one of the causes of society no longer prioritizing education for children. Therefore, this time the community service is holding a teaching and learning process program in Tongkonan with the method of implementation, namely by outreach to the community and students to invite each other to take part in the learning process with the concept of learning while playing which will be carried out in approximately 2 months. carry out 3 times a week in the Tondok Stairs environment. This work program had a very good impact on students and even parents in Pangala Village where the teaching and learning process ran smoothly and was enthusiastically welcomed by students in following the teaching and learning process with the concept of learning while playing by utilizing Tongkonan as one of the learning supports